A tele dentistry-based technique to remotely analyze maxillofacial prostheses colors using virtual color calibration (Bangladesh Journal of Medical Science, 2025)
The presented technique highlights the remote color evaluation of skin and an auricular maxillofacial prosthesis using color-corrected images facilitated by a custom 18% middle-grey virtual background in a teleconferencing software application. The International Commission on Illumination (CIE) introduced L, a* and b* color values were extracted from images using a photo editing software and plotted within an equation to evaluate the Euclidean color differences (ΔE) at different times of the day where the L, a* and b* values from the healthy ear images were considered as standard. Consistent ΔE color differences were produced and there were no significant differences in L, a* and b* color coordinates when compared statistically to professional color calibration tools. The presented technique is a viable, cost-effective alternative for evaluating color changes of auricular prostheses that can be used to guide the need for replacement utilizing a teledentistry platform.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 406-412